1H NMR analysis of the aqueous-alcoholic mixtures, prepared with softened water using Na-cationization - Kuzmin, Oleg; Topol’nik, Vera; Fatiukha, Andrew; Volkova, Ganna (My University, 2014)
Research of mechanisms of transformation of ethanol protons (ethyl rectified spirit) and water (softened by using Na-cationization) in the process of creating aqueous-alcoholic mixtures.
Keywords: 1H ЯМР спектроскопія; Na-катіонування; 1H NMR spectroscopy; Na-cationization; кафедра технології ресторанної і аюрведичної продукції